MEMBANGUN GROWTH MINDSET MAHASISWA MELALUI SUSTAINABILITY MENTAL HEALTH - Rahmawati, Setya Ayu; Maharani, Satia Nur; Lina, Hanifa Nada (Universitas Negeri Surabaya, 2025)
The mental health issues of adolescents have become a matter of concern, as during the transition period, adolescents undergo both biological and psychological changes. However, the understanding of the importance of maintaining mental health remains low, which results in a high prevalence of depression, mental health problems, and suicidal ideation among adolescents aged 15-24 years. Therefore, efforts are needed to increase adolescents' knowledge on how to maintain mental health through education. This program aims to build a growth mindset in adolescents by enhancing their understanding of mental health, so that they can better cope with mental health issues they may face. The target group for this program consists of university students and adolescents involved in the youth organization (karang taruna) of Pait Village. The program's mechanism includes preparation, presentation of materials and discussions, followed by evaluation. The implementation of this program was carried out through psychoeducation or outreach activities. The results showed that after psychoeducation on mental health, there was an increase in adolescents' understanding and interest in maintaining mental health.